Analisis Investasi Pengadaan Alat Berat untuk Penambangan Bijih Nikel Kadar Low Grade Saprolite Ore (LGSO) di PT. ANTAM (PERSERO) TBK. UBPN SULTRA - Wa Ode Nurul Anisa; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
This study discusses the selection of appropriate heavy equipment procurement options for the Low Grade Saprolite Ore (LGSO) nickel ore mining plan for 2017 until 2021, which will be exported without processing. The purpose of this study was to analyze the appropriate and profitable method of procurement of heavy equipment for PT. ANTAM (Persero) Tbk. UBPN SULTRA in the mining of LGSO nickel ore for 2017 and year 2021, the method of procurement of heavy equipment used is between companies investing mechanical equipment or performing equipment rental with contractor services. The type of research applied is the method of evaluation research (evaluation research). With the evaluation research method will be selected the best procurement of heavy equipment and can be known how far a program is achieved. Then analyzed by comparing the mining cost shown in the form of cash flow for each method of procurement of heavy equipment. In making the final decision using a comparison of Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP) as decision-making for the investment of tools or mechanical equipment leases. With a target of 2017 nickel ore of LGSO dashing 2,500,000 wmt per year, 2018 of 3,700,000 wmt per year, 2019 of 3,500,000 wmt per year, and 2020 of 3,500,000 wmt per year, and 2021 by 3,500,000 wmt annually. Based on the result of the research, it can be concluded that the value of NPV with 20% discount rate for instrument investment method is $ 373,370.89, while for tool rental method is $ 8,661,327.10. If assessed from the IRR for the tool buying method is 21.11% and for the tool lease method is 76.9%. And if assessed from PBP for tool investment method is 3.83 years, and for tool lease method is 0.89 months. So of the three criteria that meet the method of procurement of heavy equipment is profitable and profitable is the rental tool with the services of contractors.Keyword: Cash Flow, Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), LGSO